Mengungkap Tantangan Atlet Pemula dalam Menghadapi Tekanan Kompetisi - Arsyad, Muh. Nur Fajar; Latunru, Muh. Iqbal; Syahrul, Muh. Syahrul (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
This study aims to analyze the role of group dynamics and relationships between players in building strong basketball teams. A strong basketball team relies not only on individual technical ability but also on the quality of group interactions and cohesion. This study used a qualitative approach with a case study method on three university-level basketball teams in Jakarta. Data were collected through participant observation, in-depth interviews with players and coaches, and documentation analysis. The results showed that positive group dynamics significantly contributed to a 73% increase in team performance. Key factors influencing team strength include effective communication, trust between players, distributive leadership, and conflict resolution skills. Strong interpersonal relationships have been shown to improve coordination in the game, improve collective decision-making, and improve team resilience under competitive pressure. This research contributes to the development of sport psychology theory, particularly in the context of team sports, and provides practical recommendations for coaches in optimizing group dynamics to enhance basketball team performance.